A modified method of computed fluid dynamics simulation in abdominal aorta and visceral arteries. Issue 15 (18th November 2021) - Shi, Yun; Peng, Chen; Liu, Junzhen; Lan, Hongzhi; Li, Chong; Qin, Wang; Yuan, Tong; Kan, Yuanqing; Wang, Shengzhang; Fu, Weiguo
Abstract: Purpose: The flow velocity of visceral arteries was measured by 2D PCMRI to produce the patient-specific flow BC imposed on the outlets of visceral arteries in CFD simulation. This modified method aimed to improve the CFD accuracy in the abdominal aorta and visceral arteries. Methods: A volunteer underwent non-contrast-enhanced MRA to scan the abdominal aorta and visceral arteries, and 2D PCMRI to obtain the flow velocity of the aforementioned vessels. The three-dimensional geometric model was reconstructed using the MRI scan data of the abdominal aorta and visceral arteries. The flow waveforms measured by 2D PCMRI were processed and then imposed on the aortic inlet and the outlets of all visceral arteries as the flow BC. The RCR parameters of the three elements Windkessel model were modulated and imposed on the aortic outlet. CFD simulation was run in the open-source software: svSolver. The same volunteer underwent 4D flow MRI to compare the flow field with those extracted from CFD results. Results: Four specific time points in a cardiac cycle and three cross-sectional planes of aorta were selected to analyze the flow field, pressure and wall shear stress (WSS) from CFD. The flow waveforms and streamlines of CFD agreed with those of 4D flow MRI. The pressure waveforms, pressure distribution and WSS distribution from CFD conformed with the physiological condition of human body. Conclusion: These results suggest this modified CFD method may yield reasonable flow field, pressure and WSS in the abdominal aorta and visceral arteries.